Partial Degradation of Recombinant Antibody Functional Activity During Infant Gastrointestinal Digestion: Implications for Oral Antibody Supplementation - Sah, Baidya Nath P.; Lueangsakulthai, Jiraporn; Kim, Bum Jin; Hauser, Benjamin R.; Woo, Yeonhee; Olyaei, Amy; Aloia, Molly; O'Connor, Ann; Scottoline, Brian; Pastey, Manoj K.; Dallas, David C. (Frontiers in Nutrition, 2020)
Oral administration of engineered immunoglobulins has the potential to prevent enteric pathogen-induced diarrhea in infants. To prevent infection, these antibodies need to survive functionally intact in the proteolytic environment of the gastrointestinal tract. This research examined both ex vivo and in vivo the functional survival across infant digestion of palivizumab, a model FDA-approved recombinant antibody against respiratory syncytial virus (RSV) F protein. Palivizumab-fortified feed (formula or human milk), infant gastric and intestinal samples were incubated to simulate in vivo digestion (ex vivo digestion). Palivizumab-fortified human milk was also fed to infants, followed by collection of gastric and intestinal samples (in vivo digestion). Palivizumab was purified from the samples of digestate using protein G spin columns followed by filtration through molecular weight cut-off membranes (30 kDa). Palivizumab functional survival across ex vivo and in vivo digestion was determined via an anti-idiotype ELISA and an RSV plaque reduction neutralization test. Palivizumab concentration and RSV neutralization capacity both decreased when incubated in intestinal samples (ex vivo study). The concentration and neutralization activity of orally-supplemented palivizumab also decreased across infant digestion (in vivo study). These results indicate that if recombinant IgGs were selected for oral supplementation to prevent enteric infections, appropriate dosing would need to account for degradation occurring in the digestive system. Other antibody formats, structural changes, or encapsulation could enhance survival in the infant gastrointestinal tract.